Provence & the Cote d'Azur - Williams, Roger (London ; New York : Dorling Kindersley, 1995)
Gives recommendations and detailed information for visitors to Provence and the Cote d'Azur, with four sections providing an introduction to the region, an area-by-area breakdown, information on traveler's needs, and a survival guide.
Introducing Provence; writers; artists; architecture; perched villages; geography and natural history; what to buy; climate; festivals history; Provence area-by-area - Riviera and the Alpes, Maritimes, Var and the Cote d'Azur, Vouches du Rhone and Gard, Vaucluse and Alpes de Haute Provence; where to stay; restaurants; entertainment; survival guide.
Includes index.
Keywords: Provence (France) -- Guidebooks; Riviera (France) -- Guidebooks